Comparative evaluation of the effect of different growth media on in vitro sensitivity to azithromycin in multi-drug resistant pPseudomonas aeruginosa isolated from cystic fibrosis patients - Sörensen, Michael; Khakimov, Bakhodur; Nurjadi, Dennis; Boutin, Sébastien; Yi, Buqing; Dalpke, Alexander; Eigenbrod, Tatjana (Antimicrobial resistance and infection control, 2020)
Long-term treatment with azithromycin is a therapeutic option in Cystic Fibrosis (CF) patients chronically infected with P. aeruginosa. It was recently shown that azithromycin has direct antimicrobial activity when P. aeruginosa isolates are tested in Roswell Park Memorial Institute medium supplemented with fetal calf serum (RPMI 1640/FCS) by broth microdilution. We now investigated whether (i) azithromycin might also be active against multidrug resistant (MDR) P. aeruginosa isolated from CF patients and (ii) how in vitro sensitivity assays perform in synthetic cystic fibrosis sputum medium (SCFM), a medium that mimics the particular CF airway environment.In 17 (59%) out of 29 MDR P. aeruginosa CF isolates MICs for azithromycin ranged between 0.25 and 8 μg/ml and 12 isolates (41%) showed a MIC ≥512 μg/ml when measured in RPMI/FCS. In contrast, MICs were ≥ 256 μg/ml for all P. aeruginosa MDR isolates when tested in either SCFM or in conventional cation-adjusted Mueller Hinton Broth. High MIC values observed in CF adapted medium SCFM for both PAO1 and MDR P. aeruginosa CF isolates, as opposed to findings in RPMI, argue against routine azithromycin MIC testing of CF isolates.
Gesehen am 02.02.2020